Direct hyperbilirubinemia in infants with congenital heart disease. Issue 2 (24th January 2018) - Fujishiro, Jun; Sugiyama, Masahiko; Ishimaru, Tetsuya; Watanabe, Miho; Sato, Kaori; Hoshino, Noriko; Uotani, Chizue; Kutsukake, Mai; Hirata, Yoichiro; Oka, Akira
Abstract: Background: The association between congenital heart disease (CHD) and infantile cholestasis, a key finding for the diagnosis of biliary atresia (BA), has not been previously investigated. The aim of this study was therefore to investigate the characteristics of direct hyperbilirubinemia (D‐HB) in infants with CHD. Methods: All neonates admitted to the present hospital and diagnosed with CHD in 2015 and 2016 were included. D‐HB (direct bilirubin ≥ 2.0 mg/dL) at ≤60 days of age and other clinical parameters were retrospectively reviewed. Statistical analysis according to presence of D‐HB was performed using chi‐squared test or Wilcoxon rank sum test. Results: Seventy‐six patients (M:F, 36:40) were included in this study. CHD consisted of ventricular septal defect in 17, patent ductus arteriosus in 10, and other in 49. Thirteen patients (17.1%) had D‐HB at ≤60 days of age. Resolution of D‐HB (DB < 2.0 mg/dL) occurred in 10 of the 13 patients during the hospital stay, and this occurred in ≤7 days in eight of the 10 patients. Sex, gestational age, birthweight, chromosomal anomalies, need for Fontan operation for CHD repair, and/or cardiac operation were not associated with D‐HB at ≤60 days of age. Conclusion: While D‐HB was frequently observed in infants with CHD, the majority of D‐HB cases resolved spontaneously in ≤1 week. Neonatal clinical parameters or CHD status was not predictive of D‐HB. D‐HB lasting >1 week in infants with CHD should be evaluated for the cause.